The Effect of Multiliteracy Learning on Mathematical Literacy Skills of Elementary School Students - Puspita, Lily Auliya; Cahyani, Isah; Rahman, Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is motivated by the results of observations of researchers who showed that elementary school students on average were not used to receiving questions of mathematical literacy, so their abilities were low. The purpose of this study was to obtain a comprehensive picture of the effect of multiliteration learning on students' mathematical literacy abilities. The research method used was quasi-experimental research with a nonequivalent control group design. The sampling technique used was purposeful sampling with a sample size of 60 students, consisting of 30 experimental group students and 30 control group students. Data collection methods used in this study are observation sheets, tests (open-ended questions), and documentation. The data obtained were analyzed using parametric statistical test, namely t-test. The results of data analysis show that the significance level is 0,0005 <0,005, so the hypothesis is accepted, so it can be stated that there are significant differences in students' mathematical literacy skills between students who take multiliteration learning and direct learning with = 0,005 and df = 58. The application of multiliteration learning can be used as a way to improve the mathematical literacy skills of elementary school students